2016
DOI: 10.1353/pla.2016.0052
|View full text |Cite
|
Sign up to set email alerts
|

Quiet in the Library: An Evidence-Based Approach to Improving the Student Experience

Abstract: This article deals with the management of noise in an academic library by outlining an evidence-based approach taken over seven years by the University of Limerick in the Republic of Ireland. The objective of this study was to measure the impact on library users of noise management interventions implemented from 2007 to 2014 through retrospective analysis of LibQUAL+® survey data. The data indicate that readers' perceptions of the provision of quiet space in the library greatly improved in that period. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Also, our follow-up furniture survey found that 86 respondents (45%) preferred to take a phone call in a soundproof phone booth because it offered privacy and quiet. These are similar to possible solutions found in the literature: McCaffrey and Breen (2016) found evidence that "interventions such as the development of a noise policy, zoning, rearranging of furniture, removal of service points from reader spaces, and structural improvements to reduce noise travel are worthwhile interventions for libraries to consider when faced with noise problems" (p. 788).…”
Section: Discussion and Outcomessupporting
confidence: 75%
See 1 more Smart Citation
“…Also, our follow-up furniture survey found that 86 respondents (45%) preferred to take a phone call in a soundproof phone booth because it offered privacy and quiet. These are similar to possible solutions found in the literature: McCaffrey and Breen (2016) found evidence that "interventions such as the development of a noise policy, zoning, rearranging of furniture, removal of service points from reader spaces, and structural improvements to reduce noise travel are worthwhile interventions for libraries to consider when faced with noise problems" (p. 788).…”
Section: Discussion and Outcomessupporting
confidence: 75%
“…Students still value and prefer a quiet library, despite predictions about upcoming generations, but what constitutes excess or distracting noise appears to be contextual (Cowan, 2012;Crook & Mitchell, 2012;Faletar Tanackovic, Lacović, & Gašo, 2014;Khoo, Rozaklis, Hall, & Kusunoki, 2017;McCaffrey & Breen, 2016;Newcomer, Lindahl, & Harriman, 2016;Regalado & Smale, 2015;Suarez, 2007). Even very recent studies suggest that "students consider the quiet communal spaces integral to their experience of the library" (Yoo-Lee, Lee, & Velez, 2013, p. 509).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, along with these newly purposed spaces comes growing noise and lack of a quiet environment. According to the authors, the literature on noise management in libraries has grown in recent years but mostly consists of opinion-style articles with only a small number of articles that include evidence based research (McCaffrey & Breen, 2016). The lack of research studies, along with the small number of published studies focusing longitudinally on a single LibQUAL question, prompted the authors to conduct this study, which analyzes data across a seven-year period, and examines the impact of noise interventions on library users.…”
Section: Commentarymentioning
confidence: 99%
“…Concern over noise in academic libraries is not new (e.g., Luyben et al, 1981). Yet, new types of collaborative, technology-enhanced learning spaces can often make libraries seem noisier (McCaffrey & Breen, 2016;Yelinek & Bressler, 2013). Varied solutions have been attempted (McCaffrey & Breen, 2016;Yelinek & Bressler, 2013), but this study appears to be the first published investigation into using devices like NoiseSign to combat the issue.…”
Section: Commentarymentioning
confidence: 99%